CRISIS, GROWTH AND CHANGES IN SUB SAHARA AFRICA: EVIDENCE FROM KENYA - Ahmad Helmy Fuady; Erwiza Erman; Muzzar Kresna; Saiful Hakam (Jurnal Kajian Wilayah, 2017)
Since 2008, the world economy has been overshadowed by a heavy pressure from the global financial crisis. With a relatively strong global relationship, it is difficult for Kenya to fully escape the global financial crisis. Kenya has also gone through a food crisis, the post-election political crisis and the security crisis. In fact, the Kenyan economy, since the early 2000s, continues to grow without much affected by the crises. With history and economics approach, this study departs from a simple curiosity, to know how Kenya’s economic development is during the crises. This study examines three sectors that survive and thrive during times of crisis, namely agricultural sector (tea, coffee and cut flowers), infrastructure, and financial technology. In addition, this study also describes the increasing role of China in the Kenyan economy, when other donor countries are in crisis.Keywords: Crisis, agricultural sector, infrastructure development, financial technology, ChinaAbstrakSejak 2008, perekonomian dunia telahdibayangi oleh tekanan krisis keuangan global. Dengan hubungan global yang relatif kuat, sulit bagi Kenya untuk sepenuhnya keluar dari krisis tersebut. Kenya juga mengalami krisis pangan, krisis politik pasca pemilu dan krisis keamanan. Namun, ekonomi Kenya, sejak awal tahun 2000an, terus bertumbuh tanpa banyak terpengaruh oleh krisis. Dengan pendekatan sejarah dan ekonomi, penelitian ini berangkat dari keingintahuan yang sederhanatentangbagaimana perkembangan ekonomi Kenya selama krisis. Studi ini meneliti tiga sektor yang bertahan hidup dan berkembang selama masa krisis, yaitu sektor pertanian (teh, kopi dan bunga potong), infrastruktur, dan teknologi keuangan. Selain itu, studi ini juga menggambarkan peningkatan peran China dalam perekonomian Kenya, ketika negara-negara donor lainnya berada dalam krisis.Kata kunci: Krisis, sektor pertanian, pembangunan infrastruktur, teknologi keuangan, China